Analisis Peran Dan Kendala Yang Diihadapi Kepolisian Dalam Penanggulangan Perjudian Di Satuan Reskrim Unit Pidana Umum Polres Rote - Petrus, Marfilson; Sinurat, Aksi; Petrus Leo, Rudepel (CV. Multi Kreasi Media, 2024)
The Criminal Investigation Unit of the Pidum Unit of the Rote Ndao Police faces various challenges in an effort to deal with gambling crimes in the Rote area. Although the level of gambling that occurs is quite rampant, only a few have managed to bring it to the police level. This is due to the lack of community cooperation in uncovering the gambling case. There are 12 cases that have been handled over the last 3 years while the fact is that there are many gambling cases that have occurred, The author wrote this thesis proposal using a type of empirical legal research, namely by digging up information about legal phenomena in society, including the role of the police in overcoming gambling crimes at the Criminal Investigation Unit of the Pidum Unit of the Rote Ndao Police. The results of the study show that the role of the Police in the Criminal Investigation Unit of the Pidum Unit in tackling gambling crimes in Rote Ndao has been implemented quite well. There has been a decrease in gambling cases over the past 3 years. However, the role of the police in tackling gambling also still needs to be optimized. The efforts made by the police have shown positive results, but there are still some challenges that need to be addressed. The obstacles faced by the police in dealing with gambling crimes handled by the Criminal Investigation Unit of the General Crime Unit of the Rote Ndao Police are the limitations of police members in handling gambling cases, the involvement of many people in cockfighting gambling, difficulties in obtaining evidence and a lack of public awareness of the dangers of gambling.